The Refounding Cry of Humanity: A Metapoetic Analysis of César Vallejo’s “Un hombre pasa con un pan al hombro” - Morillo Sotomayor, Alex (2023)
Metapoetry is a particular fiction exercise discussed in this article with the purpose of testing new approaches to the avant-garde of the early twentieth century and its presence in Peruvian poetry. The chosen case is that of César Vallejo and the explored text is “Un hombre pasa con un pan al hombro” (‘A man passes by with a loaf of bread on his shoulder’), a poem in which the ideas about language, knowledge and culture do not resist any analysis that justifies their functioning as guarantor resources of the civilization, which therefore demands the reader to rethink the fictional nature of this poem.